A method for controlling the ash melting point of waste activated carbon-based mixed organic slurry

By mixing waste activated carbon with appropriate additives to make mixed organic slurry, the problem of difficult to regulate the ash melting point of waste activated carbon-based mixed organic slurry is solved, and stable operation and efficient gasification are achieved.

CN118287479BActive Publication Date: 2025-02-11ZHEJIANG UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410385504.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-01
Publication Date
2025-02-11
Estimated Expiration
2044-04-01

AI Technical Summary

Technical Problem

The ash melting point of waste activated carbon-based mixed organic slurry is too high or low, which affects the operating stability and safety of the gasifier, and it is difficult for the prior art to effectively regulate.

Method used

By grinding and mixing waste activated carbon with additives such as sodium salt, magnesium substances, calcium substances or aluminum substances, and adding them to an aqueous liquid to make a mixed organic slurry to regulate its ash melting point.

Benefits of technology

It realizes effective regulation of the ash melting point of waste activated carbon-based mixed organic slurry, ensures the stable operation of liquid slag discharge and furnace, and improves gasification efficiency and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118287479B_ABST
    Figure CN118287479B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for regulating the ash melting point of a waste activated carbon-based mixed organic slurry, comprising: grinding the waste activated carbon with an auxiliary agent respectively to obtain a mixed fuel for slurrying, wherein the auxiliary agent is a sodium salt, a magnesium substance, a calcium substance or an aluminum substance or an organic solid / hazardous waste rich in such substances, and realizing effective regulation of the ash melting point through a crystal phase conversion reaction between the added auxiliary agent and the ash in the waste activated carbon under high temperature conditions. The present invention realizes directional increase / reduction of the ash melting point of the waste activated carbon mixed organic slurry through component and content optimization, plays a guarantee role in realizing stable furnace operation and liquid discharge in the field of solid / hazardous waste resource utilization of water-coal slurry gasification technology, is conducive to the disposal and resource utilization of hazardous wastes, and has important environmental significance and economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of thermal treatment and resource utilization of industrial organic waste, and specifically relates to a method for regulating the ash melting point of waste activated carbon-based mixed organic slurry. Background Art

[0002] In the process of industrial production, a large amount of solid waste (including hazardous waste) is inevitably generated. At present, there are still problems such as low disposal level, low resource utilization rate, and high environmental pollution risk. Activated carbon is a porous adsorption material with important applications in many fields such as wastewater treatment, waste gas purification, and product purification. However, after reaching saturation regeneration failure, it will be converted into waste activated carbon and is included in the list of hazardous wastes in my country (HW49), which has high environmental risks. For waste activated carbon, conventional treatment methods include incineration and landfill, which are difficult to achieve resource utilization.

[0003] Water-coal slurry gasification technology has the advantages of simple furnace structure, strong adaptability to coal types, and easy control of feed. Therefore, it has been widely used as a raw material for preparing synthesis gas in gasifiers. Coal-based fluid fuel has good fluidity. As a liquid, it can be atomized to greatly improve the combustion efficiency in the gasifier. Waste activated carbon can replace coal in mixed organic slurry as the main calorific value and fixed carbon provider. High-concentration wastewater and high-calorific value organic solvents act as volatiles of coal, and cooperate with waste activated carbon to prepare mixed organic slurry for high-temperature gasification. It not only disposes of industrial organic hazardous waste, but also makes full use of the calorific value and carbon elements of organic waste to obtain high-value synthesis gas products, which has good environmental value and economic benefits. Water-coal slurry gasification technology usually uses an entrained flow furnace type and adopts a liquid slag discharge method. It requires that the melting temperature of solid gasification ash is lower than the gasification temperature. If the ash melting point is too high, the operating temperature will increase on the one hand, which will increase energy consumption, and on the other hand, it will affect the operating stability and safety of the gasifier. Therefore, the ash melting point of waste activated carbon-based mixed organic slurry becomes a key indicator in the actual operation of this technology, and its effective regulation is crucial to the operating stability and gasification efficiency of the equipment.

[0004] The research on the melting point of traditional water-coal slurry ash mainly focuses on coal, and the research on the regulation of ash melting point based on waste activated carbon is almost blank. The main raw materials of activated carbon are coal and biomass (wood or coconut shell), but its ash melting characteristics are different from those of the raw materials. The activated carbon production process undergoes high-temperature activation, acid washing and other steps. Compared with its raw materials, the content of volatile and acid-soluble components such as alkali metals and alkaline earth metal oxides such as sodium, potassium, calcium and magnesium is low, and the content of high-melting-point silicon aluminum oxides is high, which makes the melting point of waste activated carbon ash high, which is not conducive to liquid slag discharge; on the other hand, the waste activated carbon produced in the field of high-salt wastewater treatment often enriches a large amount of low-melting-point sodium salts and potassium salts in the water, which makes the melting point of waste activated carbon ash too low, posing a hidden danger to the safe operation of the gasifier. Therefore, it is of great significance to achieve the regulation of the ash melting point of waste activated carbon-based mixed organic slurry in an easy-to-implement and low-cost way. Summary of the invention

[0005] The invention provides a method for regulating the ash melting point of waste activated carbon-based mixed organic slurry. The method can be used to regulate the ash melting point of the waste activated carbon-based mixed organic slurry.

[0006] The present invention provides a method for controlling the ash melting point of a waste activated carbon-based mixed organic slurry, comprising:

[0007] Grinding the waste activated carbon and the auxiliary agent separately to obtain a mixed material, and adding the mixed material into an aqueous liquid to obtain a waste activated carbon-based mixed organic slurry;

[0008] The auxiliary agent is a sodium salt, a magnesium substance, a calcium substance or an aluminum substance, and the ash melting point of the waste activated carbon-based mixed organic slurry fuel is regulated by adding the auxiliary agent;

[0009] The aqueous liquid is water, high-concentration organic wastewater, waste organic solvent, waste emulsifier or sludge.

[0010] Preferably, the waste activated carbon is coal-based activated carbon, wood-based activated carbon or coconut shell-based activated carbon obtained by adsorbing wastewater, waste gas or product purification;

[0011] The sodium salt is Na2CO3, NaCl or solid waste with high sodium content, the magnesium substance is MgO, MgSO4 or solid waste with high magnesium content, the calcium substance is CaO, CaCO3 or solid waste with high calcium content, and the aluminum substance is Al2O3, AlCl3 or solid waste with high aluminum content.

[0012] Preferably, the ash components of the coal-based waste activated carbon are SiO2: 45% to 50%, Al2O3: 25% to 30%, Fe2O3: 11% to 15%, CaO: 6% to 11%, MgO: <3%, Na2O: <3%, K2O: <3%, SO3: 6% to 10%, TiO2: <1%, and P2O5: <1%.

[0013] Activated carbon ash is usually expressed in the form of oxides. The main components that affect the ash melting point are Al2O3, SiO2, Fe2O3, CaO, MgO, Na2O, and K2O. The decisive elements of ash melting point are generally considered to be Al and Si. Al and Si, as the highest content skeleton elements, form a series of aluminosilicate minerals that determine the main range of ash melting point. The melting point of Al2O3 itself is as high as 2054°C. The higher the content, the higher the ash melting point; and SiO2 sometimes increases the ash melting point and sometimes plays a role in fluxing. This is related to the formation of a series of aluminosilicate minerals with different melting points due to the different Si / Al ratios. Fe2O3, CaO, MgO, Na2O, and K2O are alkaline oxides. Generally speaking, alkaline oxides can generally play a role in fluxing. The ionic potential theory can explain this phenomenon to a certain extent. The acidic ions in acidic oxides have high ionic potential (ion valence / ionic radius), while the ionic potential of alkaline ions is lower. Acidic cations with high ionic potential are easy to combine with oxygen to form complex ions or polymers, while alkaline cations are oxygen donors, which can terminate the aggregation of polymers, reduce their viscosity, and show a fluxing effect.

[0014] Preferably, sodium, potassium, calcium or magnesium substances are added to the coal-based activated carbon, wherein the sodium, potassium, calcium or magnesium substances are alkali metal or alkaline earth metal compounds to reduce the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel, or aluminum substances are added to increase the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel;

[0015] The mass of the calcium substance accounts for 2% to 16% of the total mass of the ash of the calcium substance and the coal-based activated carbon, and the calcium substance is CaO. As the mass ratio of CaO increases, the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel gradually decreases;

[0016] The mass of the aluminum substance accounts for 2% to 16% of the total mass of the ash of the aluminum substance and coal-based activated carbon. The aluminum substance is Al2O3. As the mass ratio of Al2O3 increases, the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel gradually increases.

[0017] CaO itself, as an alkaline oxide, has a fluxing effect. It is easy to combine with high-melting-point acidic oxides Al and Si to form a low-temperature eutectic, thereby lowering the ash melting point, as follows Figure 1As shown in the figure, the addition of CaO increases the formation of calcium feldspar and makes it the main mineral component. When CaO is added in excess, the formation of low-melting-point feldspar no longer increases due to the limited coordination of aluminosilicate, so the ash melting point will not continue to decrease. The optimal range can be obtained through experiments. The melting point of Al2O3 itself is relatively high, reaching above 2000℃, which will drive the ash melting point to rise. On the other hand, its addition leads to the formation of mullite. Mullite ore itself can be used as a raw material to produce high-temperature refractory materials. If it continues to increase until 16%, the ash melting point can still continue to rise to 1450℃.

[0018] Further preferably, when the addition amount of Al2O3 is 8%, the flow temperature of the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel increases by 100°C;

[0019] When the addition amount of CaO is 8%, the flow temperature of the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel is reduced by 62°C.

[0020] Preferably, the ash components of the wood-based activated carbon are: SiO2: 60%-65%, Al2O3: 20%-25%, Fe2O3: 4%-8%, CaO: 2%-7%, MgO: <3%, Na2O: <3%, K2O: <3%, SO3: <3%, TiO2: <1%, P2O5: <1%.

[0021] The basic composition of wood activated carbon and coal activated carbon ash is similar, both with Si and Al as the main skeleton elements, as well as metal elements such as Fe, Ca, and Mg. The difference is that the Si content of wood activated carbon ash is about 15% higher than that of coal, while the Al content is similar, resulting in a higher melting point of wood activated carbon ash than coal.

[0022] Preferably, calcium substances or sodium salts are added to the wood-based activated carbon to reduce the ash melting point of the wood-based activated carbon-based mixed organic slurry fuel;

[0023] The mass of the sodium salt accounts for 8% to 25% of the total mass of the ash of the sodium salt and the wood-based activated carbon. The sodium salt is industrial waste salt. As the mass ratio of the industrial waste salt increases, the ash melting point of the wood-based activated carbon-based mixed organic slurry fuel gradually decreases;

[0024] The mass of the calcium substance accounts for 2% to 25% of the total mass of the ash of the calcium substance and the wood-based activated carbon. The calcium substance is CaO or limestone. As the mass ratio of the calcium substance increases, the ash melting point of the wood-based activated carbon-based mixed organic slurry fuel gradually decreases.

[0025] Na easily reacts with silicon and aluminum oxides in ash at high temperatures to form alkali metal aluminosilicates and low melting point eutectics, such as Figure 2After adding 5% Na2O, the original mullite in the ash disappears, cordierite decreases, albite increases, and it continues to decrease until 25%.

[0026] The addition of CaO increases the formation of calcium feldspar and makes it the main mineral component. Figure 2 Mullite, cordierite, corundum and silica in the original ash all disappear and transform into anorthite, and the main components of the subsequent additions are all from the anorthite family, so the ash melting point will not continue to decrease.

[0027] Further preferably, calcium substances or sodium salt substances are added to the wood-based activated carbon to reduce the ash melting point of the coal-based activated carbon-based mixed organic slurry fuel; the preferred addition amount of CaO is 8%, and the preferred addition amount of Na2CO3 is 15%.

[0028] Preferably, the ash components of the coconut shell activated carbon are: SiO2: 70%-75%, Al2O3: 20%-25%, Fe2O3: 6%-11%, CaO: 1%-5%, MgO: <3%, Na2O: <3%, K2O: <3%, SO3: <3%, TiO2: <1%, P2O5: <1%.

[0029] Preferably, calcium magnesium substances or sodium salts are added to coconut shell activated carbon to reduce the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel;

[0030] The sodium salt accounts for 8% to 25% of the total mass of the ash of the sodium salt and the coconut shell activated carbon, and the sodium salt is Na2CO3. As the mass ratio of the sodium salt increases, the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel gradually decreases;

[0031] The magnesium substance accounts for 2% to 12% (in terms of MgO) of the total mass of the ash of the magnesium substance and coconut shell activated carbon. The magnesium substance is a magnesium-containing waste. As the mass ratio of the magnesium substance increases, the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel gradually decreases. The principle of Na reducing the ash melting point is similar to that of wood activated carbon. When 5% Na2O is added, most of the mullite disappears, and the uncombined SiO2 also forms a low-temperature eutectic body, and the solid matter greatly reduces the liquid slag phase. The addition of Mg converts mullite and corundum, two high-melting-point minerals, into orthopyroxene with a lower melting point, thereby reducing the ash melting point.

[0032] Further preferably, the addition amount of Na2CO3 is 25%, and the flow temperature of the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel is reduced by 146°C;

[0033] The magnesium-containing waste is MgO, the addition amount of the MgO is 4%, and the flow temperature of the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel is reduced by 90°C.

[0034] Furthermore, the mass ratio of the sodium salt to the ash of coconut shell activated carbon is 8% to 20%, and the sodium salt is industrial waste salt.

[0035] Further preferably, the amount of industrial waste salt added is 15%, and the amount of limestone added is 16%.

[0036] Preferably, before the waste activated carbon is ground with the additives, the waste activated carbon is pretreated, including: selecting typical industrial activated carbon as raw material, crushing the activated carbon, grinding it with a coal mill, and the particle size should be below 200 meshes. Due to the complex sources of waste activated carbon, activated carbon with too high water content needs to be pre-dried first, which can be done by natural air drying or using drying equipment such as a rotary dryer. And the moisture content is reduced to below 5wt%.

[0037] Preferably, the addition and mixing of additives: In the present invention, Na-containing additives (waste salt, etc.) have a reducing effect on the three types of activated carbon, and an addition amount of 4% (calculated according to Na2CO3 and converted by the activated carbon ash content) is preferred; magnesium-containing additives can reduce the ash melting point of wood activated carbon and the effect is far better than Na, so it is preferred as a method of reducing the ash melting point of wood activated carbon. Al-containing additives (such as aluminum slag, electrolytic sludge, etc.) can increase the ash melting point. Each 4% addition increases the ash melting point by about 30°C, which is preferred for scenarios requiring high ash melting points. For additives with lower solubility such as limestone (CaO), electrolytic sludge (Al2O3, SiO2), etc., solid mixing, grinding and stirring are used; for additives with higher solubility such as waste salt, activated carbon-based mixed organic slurry can be directly added afterwards.

[0038] Preferably, water is added to make an activated carbon-based mixed organic slurry: the water mass ratio needs to be controlled between 40% and 60%, and the overall calorific value generally needs to be controlled between 15000 J / g and 17000 J / g. Due to the use of waste activated carbon, the slurry viscosity is much lower than that of coal powder, generally below 200 cPa.s, which is much lower than conventional mixed organic slurry, which also leaves room for adding additives. After the activated carbon powder is mixed with water. It needs to be fully stirred, and a stirrer is used to stir at 50 r / min for more than 80 minutes to ensure sufficient mixing and ensure that the powder particles are evenly dispersed in the water. The prepared mixed organic slurry is stored in a dedicated storage tank. The slurry is transported to the point of use through a pipeline or other conveying system.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present invention mixes the waste activated carbon with a suitable additive so that in the subsequent high-temperature gasification process, the ash component of the waste activated carbon itself reacts chemically with the additive, thereby reducing or increasing the ash melting point of the waste activated carbon-based mixed organic slurry, thereby ensuring liquid slag discharge and stable operation of the furnace.

[0041] (2) Since the regulation of ash melting point is not affected by organic components, the auxiliary agent can be selected from organic solid waste (including hazardous waste) rich in Na, K, Al, Mg, etc., and the organic solid waste and waste activated carbon ash components are calculated and formulated according to the scope of the present invention to form a mixed organic slurry. On the one hand, the calorific value of the organic solid waste can be utilized, and on the other hand, a low-temperature eutectic body is generated to effectively regulate its ash melting point. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 Provides a Factsage phase equilibrium simulation diagram of coal-based activated carbon ash at 1200°C for Examples 5 and 6;

[0043] Figure 2 Provides a Factsage phase equilibrium simulation diagram of wood activated carbon ash at 1200°C for Examples 3 and 4;

[0044] Figure 3 A Factsage phase equilibrium simulation diagram of coconut shell activated carbon ash at 1200°C is provided for Examples 1 and 2. DETAILED DESCRIPTION

[0045] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following implementation.

[0046] The measurement means provided by the specific embodiment of the present invention are as follows:

[0047] Ash melting point measurement: The ash melting point in this application follows the national standard of the coal industry "Determination of coal ash fusibility (GB / T 219-2008)". Mix the ash with 10% dextrin solution, use a mold to make a standard pyramid ash cone, place the ash cone on a corundum tray, and place it in a drying dish to dry for 3 hours. The ash melting point is tested by a microcomputer fully automatic ash melting point tester. The maximum test temperature is 1500°C, and the carbon sealing method is used to create a weak reducing atmosphere. After the ash cone is fed in, it is heated to 900°C at a rate of 17.5°C / minute, and then heated to the flow temperature at a rate of 5°C / minute. In this process, the four characteristic temperatures of the ash (deformation temperature (DT), softening temperature (ST), hemispherical temperature (HT) and flow temperature (FT)) are determined according to the specific shape of the ash cone.

[0048] Element measurement: X-ray fluorescence spectrometer is used and the sample powder is pressed into a pellet for measurement.

[0049] Addition amount: The addition amount in the present invention is relative to the ash remaining after the waste activated carbon is ashed.

[0050] In the following examples, basic parameters and some process characteristics of raw activated carbon are shown in Tables 1 and 2.

[0051] Table 1 Industrial analysis of three types of waste activated carbon (wt%)

[0052]

[0053] Table 2 Ash melting temperature of three activated carbons (℃)

[0054]

[0055] As shown in Table 1, the three activated carbons have both high fixed carbon and low ash content, and low fixed carbon and high ash content. As shown in Table 2, the ash melting points of the three activated carbons are not low, with coal ash having the lowest melting point, and the flow temperatures of wood and coconut shells being about 100°C higher than coal activated carbon.

[0056] The ash components of the three activated carbons provided in Examples 1 to 5 of the present invention are shown in Table 3.

[0057] Table 3 Ash chemical composition of three activated carbons (%)

[0058]

[0059] Example 1

[0060] Taking the coconut shell activated carbon in Table 3 as the base, 2%, 4%, 8%, 15%, 20% and 25% industrial waste salt Na salt were added to the ash content of the coconut shell activated carbon. After grinding evenly, water was added to make a mixed organic slurry fuel. The ash melting temperature was measured. The mass of the ash of the coconut shell activated carbon in this embodiment was 9.8g, 9.6g, 9.2g, 8.5g, 8g and 7.5g; the corresponding masses of Na2CO3 were 0.2g, 0.4g, 0.8g, 1.5g, 2g and 2.5g respectively. The measured ash melting point results are shown in Table 4.

[0061] Table 4 Ash melting temperature of coconut shell activated carbon mixed with Na salt (℃)

[0062]

[0063]

[0064] It can be seen from Table 4 that Na salt can significantly reduce the melting point of coconut shell activated carbon ash. When 25% Na salt is added, the ash melting point is reduced from a higher 1350°C to a lower 1206°C. In actual production, a corresponding proportion of waste sodium salt can be added to significantly reduce its ash melting point.

[0065] Na easily reacts with silicon and aluminum oxides in ash at high temperatures to form alkali metal aluminosilicates and low melting point eutectics, such as Figure 3As shown, when 5% Na2O is added, most of the mullite disappears, uncombined SiO2 also forms a low-temperature eutectic, the solid matter is greatly reduced and the liquid slag phase is increased.

[0066] Example 2

[0067] Taking the coconut shell activated carbon in Table 3 as the base, 2%, 4%, 8%, 12%, and 16% MgO industrial magnesium slag was added to the ash content of the coconut shell activated carbon, and then water was added to make a mixed organic slurry fuel. The ash melting temperature was measured. The mass of the ash of the coconut shell activated carbon in this embodiment was 9.8g, 9.6g, 9.2g, 8.8g, and 8.4g, and the corresponding mass of MgO was 0.2g, 0.4g, 0.8g, 1.2g, and 1.6g, respectively. The measured ash melting point results are shown in Table 5.

[0068] Table 5 Ash melting temperature of coconut shell activated carbon mixed with Mg-containing substances

[0069]

[0070] It can be seen from Table 5 that MgO has a good effect on reducing the melting point of coconut shell activated carbon ash, and the effect is better than that of Na salt. The addition of only 4% can reduce the temperature by about 90℃ to 1263℃, but the effect is not obvious in the range of greater than 4% and less than or equal to 16%, so 4% is the best addition amount.

[0071] Depend on Figure 3 It can be seen that the addition of Mg converts mullite and corundum, two high melting point minerals, into orthopyroxene with a lower melting point, thereby reducing the ash melting point. In actual production, waste Mg salts or magnesium-containing waste materials in fertilizer production can be added to reduce the ash melting point.

[0072] Example 3

[0073] Taking the wood activated carbon in Table 3 as the base, 2%, 4%, 8%, 15%, 20% and 25% industrial waste salt Na salt (calculated as Na2CO3) were added to the ash content of the wood activated carbon, the mixture was ground evenly and then added with water to make a mixed organic slurry fuel. The ash melting temperature was measured. The ash mass of the wood activated carbon in this embodiment was 9.8g, 9.6g, 9.2g, 8.5g, 8g and 7.5g, and the corresponding masses of Na2CO3 were 0.2g, 0.4g, 0.8g, 1.5g, 2g and 2.5g respectively. The measured ash melting point results are shown in Table 6.

[0074] Table 6 Ash melting temperature of wood activated carbon mixed with Na salt (℃)

[0075]

[0076] From Table 6, we can see that Na salt can also effectively reduce the ash melting point of wood activated carbon. An addition of 8% can reduce the ash melting point to 1306°C, and a high addition of 25% can reduce the ash melting point from 1356°C to 1171°C. Na reacts easily with silicon and aluminum oxides in the ash at high temperatures to form alkali metal aluminosilicates and low melting point eutectics, such as Figure 2 After adding 5% Na2O, the original mullite in the ash disappears, cordierite decreases, albite increases, and it continues to decrease until 25%.

[0077] Example 4

[0078] Taking the wood activated carbon in Table 3 as the base, 2%, 4%, 8%, 12% and 16% gypsum CaO were added to the ash content of the wood activated carbon, and the mixed organic slurry fuel was made after grinding evenly and adding water. The ash melting temperature was measured. The ash mass of the wood activated carbon in this embodiment was 9.8g, 9.6g, 9.2g, 8.8g and 8.4g, and the corresponding CaO mass was 0.2g, 0.4g, 0.8g, 1.2g and 1.6g respectively. The measured ash melting point results are shown in Table 7.

[0079] Table 7 Ash melting temperature of wood activated carbon mixed with CaO (℃)

[0080]

[0081]

[0082] From Table 7, we can see that for wood activated carbon, Ca substances have a more positive effect on reducing the ash melting point than Na. The addition of only 4% can reduce the ash melting point by about 100℃ to 1259℃, but the effect is not obvious in the range of 4% to 16%, so 4% is the best addition. The addition of CaO increases the formation of calcium feldspar and becomes the main mineral component. Figure 2 Mullite, cordierite, corundum and silica in the original ash all disappear and transform into anorthite, and the main components of the subsequent additions are all anorthite family, so the ash melting point will not continue to drop. Limestone, sludge, etc. can be added in actual production.

[0083] Example 5

[0084] Taking the coal-based activated carbon in Table 3 as the base, 2%, 4%, 8% and 16% kaolin Al2O3 were added to the ash content of the coal-based activated carbon, and the mixture was ground evenly and then added with water to make a mixed organic slurry fuel. The ash melting temperature was measured. The ash mass of the wood activated carbon in this embodiment was 9.8g, 9.6g, 9.2g, 8.8g and 8.4g, and the mass of Al2O3 was 0.2g, 0.4g, 0.8g, 1.2g and 1.6g respectively. The measured ash melting point results are shown in Table 8.

[0085] Table 8 Ash melting temperature of coal-based activated carbon mixed with Al2O3 (℃)

[0086]

[0087] From Table 8, we can see that adding alumina can increase the melting point of coal-based activated carbon ash. When the addition amount is 8%, it can increase by 100℃ to 1340℃. The melting point of Al2O3 itself is relatively high, reaching more than 2000℃, which will drive the ash melting point to rise. Figure 1 As shown, on the other hand, its addition generates mullite, and mullite ore itself can be used as a raw material to produce high-temperature refractory materials. The ash melting point can continue to rise to 1450°C when the ash melting point continues to increase until 16%. In actual production, if high-temperature working conditions are encountered and the ash melting point of the mixed slurry is low, aluminum-containing wastes such as kaolin and electrolyte mud can be added to increase the ash melting point to adapt to high-temperature working conditions.

[0088] Example 6

[0089] Taking the coal-based activated carbon in Table 3 as the base, 4%, 8%, 12%, and 16% limestone CaO were added to the ash content of the coal-based activated carbon, and the mixture was ground evenly and then added with water to make a mixed organic slurry fuel. The ash melting temperature was measured. The ash mass of the wood activated carbon in this embodiment was 9.8g, 9.6g, 9.2g, 8.8g, and 8.4g, and the mass of CaO was 0.2g, 0.4g, 0.8g, 1.2g, and 1.6g, respectively. The measured ash melting point results are shown in Table 9.

[0090] Table 9 Ash melting temperature of coal-based activated carbon mixed with CaO

[0091]

[0092] From Table 9, it can be seen that when the CaO addition reaches 8%, the ash melting point has a significant effect of decreasing, but no obvious effect is seen before 4%, and after the addition exceeds 8%, the ash melting point only decreases slightly. CaO itself has a fluxing effect as an alkaline oxide, and it is easy to combine with the high-melting-point acidic oxides Al and Si to form a low-temperature eutectic, thereby reducing the ash melting point. Figure 1 As shown in the figure, the addition of CaO increases the formation of calcium feldspar and makes it the main mineral component. However, when excessive CaO is continuously added, the formation of low-melting-point feldspar no longer increases due to the limited coordination of aluminosilicate, and therefore the ash melting point will not continue to decrease.

Claims

1. A method for controlling the ash melting point of waste activated carbon-based mixed organic slurry, characterized in that: include: Grinding the waste activated carbon and the auxiliary agent separately to obtain a mixed material, and adding the mixed material into an aqueous liquid to obtain a waste activated carbon-based mixed organic slurry; The auxiliary agent is a sodium salt, a magnesium substance, a calcium substance or an aluminum substance, and the ash melting point of the waste activated carbon-based mixed organic slurry fuel is regulated by adding the auxiliary agent; The aqueous liquid is water, organic wastewater, waste organic solvent, waste emulsifier or sludge; The waste activated carbon is wood-based activated carbon or coconut shell-based activated carbon for adsorbing wastewater, waste gas or product purification; The ash components of the coconut shell activated carbon are as follows: SiO2: 70%, Al2O3: 20%~25%, Fe2O3: 6%~11%, CaO: 1%~5%, MgO: <3%, Na2O: <3%, K2O: <3%, SO3: <3%, TiO2: <1%, P2O5: <1%; Adding magnesium substances to coconut shell activated carbon to reduce the ash melting point of coconut shell activated carbon-based mixed organic slurry fuel; The magnesium substance accounts for 2% to 12% of the total mass of the ash of the magnesium substance and the coconut shell activated carbon. The magnesium substance is magnesium-containing waste. As the mass ratio of the magnesium substance increases, the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel gradually decreases. The ash content of the wood-based activated carbon is SiO2: 60%~65%, Al2O3: 20%~25%, Fe2O3: 4%~8%, CaO: 2%~7%, MgO: <3%, Na2O: <3%, K2O: <3%, SO3: < 3%, TiO2: <1%, P2O5: <1%; Adding calcium substances or sodium salts to wood-based activated carbon to reduce the ash melting point of wood-based activated carbon-based mixed organic slurry fuel; The mass of the sodium salt accounts for 8% to 25% of the total mass of the ash of the sodium salt and the wood-based activated carbon. The sodium salt is industrial waste salt. As the mass ratio of the industrial waste salt increases, the ash melting point of the wood-based activated carbon-based mixed organic slurry fuel gradually decreases; The mass of the calcium substance accounts for 2% to 25% of the total mass of the ash of the calcium substance and the wood-based activated carbon. The calcium substance is CaO or limestone. As the mass ratio of the calcium substance increases, the ash melting point of the wood-based activated carbon-based mixed organic slurry fuel gradually decreases.

2. The method for controlling the ash melting point of waste activated carbon-based mixed organic slurry according to claim 1, characterized in that: Adding sodium salt to coconut shell activated carbon to reduce the ash melting point of coconut shell activated carbon-based mixed organic slurry fuel; The sodium salt accounts for 8% to 25% of the total mass of the ash of the sodium salt and coconut shell activated carbon. The sodium salt is Na2CO3. As the mass ratio of the sodium salt increases, the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel gradually decreases.

3. The method for controlling the ash melting point of waste activated carbon-based mixed organic slurry according to claim 2, characterized in that: The addition amount of Na2CO3 is 25%, and the flow temperature of the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel is reduced by 146°C; The magnesium-containing waste is MgO, the addition amount of the MgO is 4%, and the flow temperature of the ash melting point of the coconut shell activated carbon-based mixed organic slurry fuel is reduced by 90°C.

Citation Information

Patent Citations

  • Harmless treatment system and method with synergism of plasma gasification furnace and garbage incineration power plant

    CN110715297A

  • Fluxing agent for reducing melting point of coal ash

    CN111534355A